Fractionation and phytochemical composition of an ethanolic extract of Ziziphus nummularia leaves: antioxidant and anticancerous properties in human triple negative breast cancer cells - Abdallah, Rola; Shaito, Abdullah A.; Badran, Adnan; Baydoun, Serine; Sobeh, Mansour; Ouchari, Wafae; Sahri, Nihad; Eid, Ali H.; Mesmar, Joelle Edward; Baydoun, Elias (Frontiers in Pharmacology, 2024)
Natural products have long been utilized in traditional medicine as remedies to improve health and treat illnesses, and have had a key role in modern drug discovery. Recently, there has been a revived interest in the search for bioactives from natural sources as alternative or complementary modalities to synthetic medicines; especially for cancer treatment, which incidence and mortality rates are on the rise worldwide. Ziziphus nummularia has been widely used in traditional medicine for the treatment of various diseases. Its traditional uses and numerous ethnopharmacological properties may be attributed to its richness in bioactive metabolites. However, its phytochemical composition or chemopreventive effects against the aggressive triple negative breast cancer (TNBC) are still poorly explored. Here, phytochemical composition of an ethanolic extract of Z. nummularia leaves (ZNE) and its chromatographically isolated fractions was identified both qualitatively by spectrophotometric assays and analytically by HPLC-PDA-MS/MS. The antiproliferative effects of ZNE were tested in several cancer cell lines, but we focused on its anti-TNBC effects since they were not explored yet. The anti-cancerous potential of ZNE and its fractions was tested in vitro in MDA-MB-231, a TNBC cell line. Results showed that ZNE and its Fraction 6 (F6) reduced the viability of MDA-MB-231 cells. F6 decreased MDA-MB-231 viability more than crude ZNE or its other fractions. ZNE and F6 are rich in phytochemicals and HPLC-PDA-MS/MS analysis identified several metabolites that were previously reported to have anticancerous effects. Both ZNE and F6 showed potent antioxidant capacity in the DPPH assay, but promoted reactive oxygen species (ROS) production in MDA-MB-231 cells; an effect which was blunted by the antioxidant N-acetyl cysteine (NAC). NAC also blunted ZNE-and F6-induced reduction in TNBC cell viability. We also demonstrated that ZNE and F6 induced an arrest of the cell cycle, and triggered apoptosis-and autophagy-mediated cell death. ZNE and F6 inhibited metastasis-related cellular processes by modifying cell migration, invasion, and adhesion. Taken together, our findings reveal that Z. nummularia is rich in phytochemicals that can attenuate the malignant phenotype of TNBC and may offer innovative avenues for the discovery of new drug leads for treatment of TNBC and other cancers.